Psychological impact and associated factors with the COVID-19 pandemic and social distancing in Minas Gerais, Brazil: Cross-sectional study (Research, Society and Development, 2021)
The emergence of a pandemic can have important impacts on the mental health of the affected populations. The objective of this research was to identify the psychological impact and associated factors during a period of the COVID-19 pandemic and social distance in a sample of the inhabitants of the state of Minas Gerais, Brazil. This cross-sectional study had a descriptive character with a quantitative approach. We used a sociodemographic questionnaire and the Self Report Questionnaire (SRQ-20) to assess the suspicion of Common Mental Disorders (CMD). The survey obtained 619 responses through an online questionnaire. The prevalence of CMD in the sample was 42.6% (CI95%: 38.7-46.5). We found associations between CMD and young participants, women, singles, college students, those participants who had a diagnosed mental disorder, who had their routine, studies and family income affected and were very dissatisfied with the information about COVID-19 released by the public health authorities and very concerned about the influence that COVID-19 will have on their studies. The COVID-19 pandemic promoted a relevant psychological impact in this sample of the population of Minas Gerais.